Proton control of amino acid transport and protein trafficking - Wu, Z (2020)
Protons play a key role in various biological process ranging from substrate binding, protein conformational change, oligomerisation processes as well as altering the chemical environment within the protein. Computational techniques such as molecular dynamics or quantum mechanics calculations are excellent tools at tracking the proton as well as examining its effect on the protein.